2017
DOI: 10.47672/jsm.287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Management Efficiency on Financial Performance of Savings and Credit Societies in Kenya

Abstract: Purpose: The purpose of this study was to evaluate the effect of management efficiency on financial performance of savings and credit societies in Kenya.Methodology: The study employed an explanatory research design. The target population was 83 registered deposit taking SACCO’s in Kenya that have been in operation for the last five years. The sample size for the study was all 83 SACCOs that have remained in existence since 2011-2015. Census methodology was used in the study.  Both primary and secondary source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…The result of the model is as per the prior expectation and in line with x-efficiency theory, which says efficient firms (lower cost) tend to earn higher profit. The result is consistent with the findings of Atsango (2018), Ashenafi and Cherinet (2018), Barus et al (2017) and Zergaw (2015), who found that OE has a negative and statistically significant effect on profitability, but against the finding of Ochingo and Muturi (2018), Ngumo and Collins (2017), Fujo and Ali (2016) and Hesborn et al (2016), who found that OE has a positive and significant effect on profitability; perhaps, this can be attributed to external factors, which are responsible for such variations.…”
Section: Model Results For Profitability (Roa)supporting
confidence: 93%
See 4 more Smart Citations
“…The result of the model is as per the prior expectation and in line with x-efficiency theory, which says efficient firms (lower cost) tend to earn higher profit. The result is consistent with the findings of Atsango (2018), Ashenafi and Cherinet (2018), Barus et al (2017) and Zergaw (2015), who found that OE has a negative and statistically significant effect on profitability, but against the finding of Ochingo and Muturi (2018), Ngumo and Collins (2017), Fujo and Ali (2016) and Hesborn et al (2016), who found that OE has a positive and significant effect on profitability; perhaps, this can be attributed to external factors, which are responsible for such variations.…”
Section: Model Results For Profitability (Roa)supporting
confidence: 93%
“…The model result is as per the prior expectation and in line with x-efficiency theory, which states that efficient firms (lower cost) tend to earn higher profit, which could result in financial sustainability. The result is consistent with the findings of Atsango (2018), Ashenafi and Cherinet (2018), Barus et al (2017) and Zergaw (2015), who found that OE has a negative effect on financial performance. However, the model result is opposite to the finding of Melesse ( 2019), Abate et al (2013) and Nyamsogoro (2010), who found that OE has a positive effect on financial sustainability.…”
Section: Model Results For Financial Sustainability (Fss)supporting
confidence: 92%
See 3 more Smart Citations